2019
DOI: 10.1080/21711976.2019.1586140
|View full text |Cite
|
Sign up to set email alerts
|

Structural confirmation of the 24-item Environmental Attitude Inventory / Confirmación estructural del Inventario de Actitudes Ambientales de 24 ítems

Abstract: Despite an ever-increasing use of the Environmental Attitude Inventory (EAI), few studies have aimed at checking the dimensional structure of its 24item version and particularly the structure of the subdimensions and its two main dimensions: utilization and preservation of the environment. Structural analyses confirmed the strength of the structure suggested by Milfont and Duckitt (2010) particularly well. Pro-environmental behaviors can be predicted by this scale, mainly through the dimension of preservation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
0
10
0
2
Order By: Relevance
“…Numerous authors have examined the interaction between individuals and their natural environment. Researchers have investigated various constructs, including environmental values [36,37], nature relatedness [38,39], connectedness to nature [40], environmental behaviors [41], environmental attitudes [42], eco-anxiety [19,20,23,25,43], and environmental responsibility [44][45][46][47].…”
Section: Understanding the Interaction Between The Individual And The...mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous authors have examined the interaction between individuals and their natural environment. Researchers have investigated various constructs, including environmental values [36,37], nature relatedness [38,39], connectedness to nature [40], environmental behaviors [41], environmental attitudes [42], eco-anxiety [19,20,23,25,43], and environmental responsibility [44][45][46][47].…”
Section: Understanding the Interaction Between The Individual And The...mentioning
confidence: 99%
“…It was also found that individual values play a significant role in environmental decision making, with biospheric and altruistic values promoting sustainability behaviors [63]. Moreover, it has been revealed that environmental consciousness among rural inhabitants is a regulating ethos governing social practices [89] and that environmental values are related to environmental preservation [42]. Additionally, research has also shown that reading pro-environmental materials, such as Pope Francis's encyclical, can increase a belief in and moralization of climate change [90].…”
Section: Understanding the Interaction Between The Individual And The...mentioning
confidence: 99%
“…Estos autores analizan el impacto que los factores contextuales, medidos a nivel local, tienen sobre el comportamiento proambiental individual y también la interacción entre los factores contextuales locales y diversas variables individuales como las actitudes ambientales. Teniendo en cuenta esta circunstancia, surge la necesidad de llevar a cabo una investigación en el contexto chino que: (1) analice los factores actitudinales y contextuales determinantes de varias tipologías de conductas ambientales; (2) utilice una perspectiva multidimensional del ambientalismo, ya que la literatura previa ha incidido en la necesidad de tener en cuenta el carácter multidimensional de las actitudes ambientales por su mejor adecuación para analizar transculturalmente las relaciones complejas entre las personas y el medio ambiente (Ajdukovic et al, 2019; Amérigo et al, 2020; Domingues et al, 2019); y (3) profundice en el estudio del efecto moderador de los factores contextuales.…”
Section: Comportamiento Proambiental En China: Analizando El Impacto ...unclassified
“…These authors analyse the impact that contextual factors, measured at the local level, have on individual pro-environmental behaviour and also the interaction between local contextual factors and various individual variables such as environmental attitudes. In light of the above, there is a need to conduct research in the Chinese context that: (1) analyses the attitudinal and contextual factors that determine various types of environmental behaviour; (2) uses a multidimensional perspective on environmentalism, as previous literature has emphasized the need to take into account the multidimensional nature of environmental attitudes because such an approach is better suited to analysing, transculturally, complex relationships between people and the environment (Ajdukovic et al, 2019; Amérigo et al, 2020; Domingues et al, 2019); and (3) further explores the moderating effect of contextual factors.…”
mentioning
confidence: 99%
“…Concernant la portée persuasive des éléments, celle-ci a été évaluée à deux niveaux. Au niveau attitudinal à l'aide de l'inventaire des attitudes environnementales (EAI), validées en 20 items [1]. Ainsi qu'au niveau intentionnel, c'est-à-dire, les comportements que les participants déclarent vouloir mettre en oeuvre.…”
Section: éTude 2 Méthodeunclassified